Enzyme‐based detection of epoxides using colorimetric assay integrated with smartphone imaging. (24th February 2020) - Gul, Ijaz; Bogale, Tadesse Fantaye; Deng, Jiao; Chen, Yong; Fang, Ruiqin; Feng, Juan; Tang, Lixia
Abstract: Epoxides are widely used chemicals, the determination of which is of paramount importance. Herein, we present an enzyme‐based approach for noninstrumental detection of epoxides in standard solution and environmental samples. Halohydrin dehalogenase (HheC) as a biological recognition element and epichlorohydrin as a model analyte were evaluated for sensing. The detection is based on the color change of the pH indicator dye bromothymol blue caused by the HheC‐catalyzed ring‐opening of the epoxide substrate. The color change is then exploited for the determination of epoxide using a smartphone as an image acquisition and data processing device, eliminating the need for computer‐based image analysis software. The color parameters were systematically evaluated to determine the optimum quantitative analytical parameter. Under optimal conditions, the proposed enzyme‐based detection system showed a linear range of 0.13–2 mM with a detection limit of 0.07 mM and an assay time of 8 Min. In addition, the repeatability expressed as relative standard deviation was found to be below 5% ( n  = 6). Validation with gas chromatographic analyses showed that the proposed enzyme‐based epoxide detection could be an alternative way in the quantitative determination of epoxides, and particularly useful in resource‐limited settings. Abstract : Schematic illustration of the enzyme‐based epoxide detection. The detection scheme is based on the use of halohydrin dehalogenase that catalyzes epoxide substrate accompanying consumption of proton. The increase in pH is sensed by a pH sensitive dye.